Clinical Outcomes of Transcatheter Aortic Valve Replacement in Nonagenarians: A Systematic Review and Meta-Analysis - Yan Liu; Yu Du; Mingjie Fu; Yue Ma; Deguang Wang; Jinglin Zhang; Wei Liu; Yingxin Zhao; Yujie Zhou (Journal of Interventional Cardiology)
Objectives. To compare the incidence of mortality and complications between nonagenarians and younger patients undergoing transcatheter aortic valve replacement (TAVR). Background. TAVR has become an alternative treatment for nonagenarian patients with severe aortic stenosis. Previous studies have reported conflicting results regarding the clinical outcomes between nonagenarians and younger patients who underwent TAVR. Methods. We searched PubMed, EMBASE, and Cochrane Library databases with predefined criteria from the inception dates to July 8, 2018. The primary clinical endpoint was 30-day and 1-year all-cause mortalities. Secondary outcomes were considered the rates of stroke, myocardial infarction, any bleeding, any acute kidney injury, any vascular complications, new pacemaker implantation, and conversion to surgical aortic valve replacement. Results. A total of 5 eligible studies with 25,371 patients were included in this meta-analysis. Compared with younger patients who underwent TAVR, nonagenarians had a significantly higher mean Society of Thoracic Surgeons score (STS score) (MD, 2.80; 95%CI: 2.58, 3.30; P<0.00001) and logistic European System for Cardiac Operative Risk Evaluation (logistic EuroSCORE) (MD, 2.72; 95%CI: 1.01, 4.43; P=0.002). Nonagenarians were associated with significantly higher 30-day mortality (6.2% vs. 3.7%; OR, 1.73; 95%CI: 1.49, 2.00) and 1-year mortality (15.5% vs. 11.8%; OR, 1.39; 95%CI: 1.26, 1.53), without significant statistical heterogeneity. Nonagenarians were associated with significantly increased rates of major or life-threatening bleeding, vascular complications and stroke of 20%, 35%, and 32%, respectively. There were no significant differences in the rate of myocardial infarction, stage 2 or 3 acute kidney injury, new pacemaker implantation, or conversion to surgical aortic valve replacement. Conclusions. Nonagenarians showed worse clinical outcomes than younger patients after TAVR, while the incidence of mortality was acceptable. TAVR remains an option for nonagenarian patients with severe aortic stenosis and should be comprehensively evaluated by the heart valve team.